Chapter Il significato incarnato dell'architettura - Johnson, Mark L. (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Reflects on the nature of human meaning making through architecture. Meaning mak-ing is understood to be situated, relational, qualitative, dynamic and enacted. To appre-ciate the significance of architecture we need to understand how meaning is structured through the body. Some image-body schemas include containment, verticality, balance, forces and motion. Architecture's moral imperative is to creatively transform the condi-tions of human habitation and interaction.